Anti-angiogenic agents for NSCLC following first-line immunotherapy: Rationale, recent updates, and future perspectives. (May 2023) - Reck, Martin; Popat, Sanjay; Grohé, Christian; Corral, Jesus; Novello, Silvia; Gottfried, Maya; Brueckl, Wolfgang; Radonjic, Dejan; Kaiser, Rolf; Heymach, John
Highlights: Immunotherapy ± chemotherapy is a first-line treatment of choice in advanced NSCLC. There is a major unmet need for treatment options after immunotherapy. Targeting VEGF-promoted angiogenesis may reduce immunosuppression. Anti-angiogenics may reinstate and enhance the effect of subsequent therapies. Nintedanib, ramucirumab and other anti-angiogenics show promise after immunotherapy. Abstract: The implementation of immune checkpoint inhibitors (ICIs), with or without chemotherapy, as first-line treatment for patients who do not have actionable mutations has proved to be a major paradigm shift in the management of advanced non-small cell lung cancer (NSCLC). However, the transition of ICIs, such as pembrolizumab and nivolumab, to a first-line setting has left an unmet need for effective second-line treatment options, which is an area of intense research. In 2020, we reviewed the biological and mechanistic rationale for anti-angiogenic agents in combination with, or following, immunotherapy with the aim of eliciting a so called 'angio-immunogenic' switch in the tumor microenvironment. Here, we review the latest clinical evidence of the benefits of incorporating anti-angiogenic agents into treatment regimens. While there is a paucity of prospective data, several recent observational studies indicate that the marketed anti-angiogenic drugs, nintedanib or ramucirumab, are effective in combination with docetaxel following immuno-chemotherapy. Addition of anti-angiogenics, like bevacizumab, have also demonstrated clinical benefit when combined with first-line immuno-chemotherapy regimens. Ongoing clinical trials are assessing these agents in combination with ICIs, with encouraging early results (e.g., ramucirumab plus pembrolizumab in LUNG-MAP S1800A). Also, several emerging anti-angiogenic agents combined with ICIs are currently being assessed in phase III trials following immunotherapy, including lenvatinib (LEAP-008), and sitravatinib (SAPPHIRE) It is hoped that these trials will help expand second-line treatment options in patients with NSCLC. Areas of focus in the future will include further molecular dissection of the mechanisms of resistance to immunotherapy and the various response–progression profiles to immunotherapy observed in the clinic and the monitoring of the dynamics of immunomodulation over the course of treatment. Improved understanding of these phenomena may help identify clinical biomarkers and inform the optimal use of anti-angiogenics in the treatment of individual patients.